Educational mission of Mariia Kultaieva in Ukrainian philosophy - Євген Бистрицький (Філософія освіти)
Words of gratitude and deep respect for Maria Dmitrivna Kultaeva from her colleague and friend Yevhen Kostyantynovych Bystrytsky.